Pendidikan Karakter Berjiwa Wirausaha Melalui Pembuatan Kerajinan Recycle Di SDN Kawatan No.19 Surakarta - Fitriyani, Ria Wulan, Dra. Ratnasari Diah Utami M.Si, M.Pd (2017)
The research aims to describe: 1) Character building of entrepreneurial through craft-making recycle in the SDN. Kawatan No. 19 Surakarta. 2) Constraints faced on Character building of entrepeneurial through craft-making recycle in the SDN. Kawatan No. 19 Surakarta. 3) The solution of the obstacles encountered in Character building of ntrepeneurial through craft-making recycle in the SDN. Kawatan No. 19 Surakarta. This research used a qualitative research with descriptive research design. The informant in this research are the head master, teacher coordinator, students and parents. The data collection techniques used were nterviews, observative, documentation and questionaire. Testing the vslidity of the data obtained using the triangulation of source and teachniques. The stages of data analysis in this research is data collection, data reduction, data sentation, and conclusion. The results of this research character building of entrepeneurial seen that students are more creative, innovative and results-oriented tasks, more dare to take risks and leadership. The constraints in character building of entrepeneurial through the creation of recycle is a lack of confidence in the students to sell crafts recycle, the lack of concern for the environment to dispose of waste is not in place, the students trouble istinguishing organic and anorganic waste, the students do not follow the activities on Saturday and forgot to bring equipment used. The solutions of the head master and teachers coordinators face constrains in character building of entrepeneurial through craft-making is the motivation recycle selling crafts, socializing with parents and loaned equipment. Keywords: character, entrepreneurial, recycle